2014
DOI: 10.7888/juoeh.36.257
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Tendon Injuries Accompanying Distal Radius Fractures Using Volar Locking Plates

Abstract: We examined 6 cases of tendon injuries that accompanied distal radius fractures using volar locking plate between April 2006 and March 2012. Male: one case, female: five cases, average age 57.0 (33~70) years old. The fracture type was A2 in one case, A3 in four cases, and C2 in one case by AO classification. The average period for operation waiting was 2.7 days. We analyzed the time of occurrence of tendon rupture (extensor pollicis longus (EPL)・flexor pollicis longus (FPL)), the existence or not of screw prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The average time to rupture after VLP fixation is around 3 months. 10 After this time, extensor tendon injury as a complication of VLPs is less likely but can still be considered, as 1 case study found delayed rupture of the extensor digitorum communis linked to dorsal screw prominence 7 years after initial fixation. 8 Multiple extensor tendons may rupture, potentially presenting at different times postoperatively.…”
Section: Clinical Presentation Of Extensor Tendon Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average time to rupture after VLP fixation is around 3 months. 10 After this time, extensor tendon injury as a complication of VLPs is less likely but can still be considered, as 1 case study found delayed rupture of the extensor digitorum communis linked to dorsal screw prominence 7 years after initial fixation. 8 Multiple extensor tendons may rupture, potentially presenting at different times postoperatively.…”
Section: Clinical Presentation Of Extensor Tendon Complicationsmentioning
confidence: 99%
“…13 In individual studies, the reported risk of extensor tendon rupture ranges from 0% to 12.5% (Table 1). [2][3][4]10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The reported risk of extensor tendon irritation or tenosynovitis ranges from 1.1% to 23.9%.…”
Section: Extensor Tendon Injury Following Vlpmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensor tendon rupture has primarily been attributed to screw prominence. 9 The flexor pollicis longus (FPL) is the most common flexor tendon to rupture in association with VLP fixation as it courses directly over the rim of the distal radius. 10,11 The exact cause of FPL tendon ruptures remains unknown; however, reports suggest that prominence of the volar plate over the volar rim of the distal radius may contribute to higher rupture rates.…”
Section: Introductionmentioning
confidence: 99%